2011
DOI: 10.4314/ijbcs.v5i1.68104
|View full text |Cite
|
Sign up to set email alerts
|

Potential enterobacteria risk factors associated with contamination of lettuce (</i>Lactuca sativa</i>) grown in the peri-urban area of Abidjan (Côte d’Ivoire)

Abstract: This study was conducted to determine the risk factors associated with the contamination of lettuce grown in the suburban area of Abidjan. A total of 216 samples were collected. Total aerobic bacterial counts and Enterobacteriaceae were investigated on soil, fertilizer, irrigation water and lettuce samples. Mean values of total aerobic count for sites 1 and 2 were 9.97 log 10 cfu/g and 8.20 log 10 cfu/g for the manure respectively, and 8.11 log 10 cfu/g for the soil of both sites. Lettuce samples from the mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…The same flora had also been identified in urban production lettuce in other works (Mohammad et al, 2013). Similarly, Koffi et al (2011), Mngoli & Ng'ong'ola-Manani, (2014 and Akusu et al (2016) isolated enterobacteria in lettuce in similar studies in Côte d'Ivoire, Malawi and Nigeria, respectively. The strong presence of these microfloras would translate into a marked deficit of good production and hygiene practices in the study site.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The same flora had also been identified in urban production lettuce in other works (Mohammad et al, 2013). Similarly, Koffi et al (2011), Mngoli & Ng'ong'ola-Manani, (2014 and Akusu et al (2016) isolated enterobacteria in lettuce in similar studies in Côte d'Ivoire, Malawi and Nigeria, respectively. The strong presence of these microfloras would translate into a marked deficit of good production and hygiene practices in the study site.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have reported this form of contamination. For Koffi et al (2011) in Côte d'Ivoire, Abbou et al (2014) in Morocco and Holvoet et al (2014b) in Belgium, irrigation water from urban vegetable crops was the main source of microbial contamination of production. Coagulase positive Staphylococcus aureus has been reported in work in lettuce in Brazil (Cé sar et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, it is important to monitor the quality of water used for irrigation in agriculture, and specially that used for fresh vegetables in Ouagadougou. During the last fifteen years, some studies (Amoah et al, 2004;Raschid-Sally and Jayakody, 2009;Diogo et al, 2010;Koffi-Nevry et al, 2011;Cobbina et al, 2013) highlighted contamination risks by analyzing contamination of vegetables by parasite linked to the quality of irrigation water in West Africa. But in Burkina Faso in particular and generally in the sub-Sudanian semi-arid condition, characterized by important water scarcity and highly increasing pressures on water resources there is still gaps to fill.…”
Section: Introductionmentioning
confidence: 99%